2013
DOI: 10.1523/jneurosci.5423-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Impaired D-Serine-Mediated Cotransmission Mediates Cognitive Dysfunction in Epilepsy

Abstract: The modulation of synaptic plasticity by NMDA receptor (NMDAR)-mediated processes is essential for many forms of learning and memory. Activation of NMDARs by glutamate requires the binding of a coagonist to a regulatory site of the receptor. In many forebrain regions, this coagonist is D-serine. Here, we show that experimental epilepsy in rats is associated with a reduction in the CNS levels of D-serine, which leads to a desaturation of the coagonist binding site of synaptic and extrasynaptic NMDARs. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…In addition, disruption of adenosine and D‐serine signaling mechanisms associates with post‐synaptic molecular changes and lower seizure threshold (Klatte et al . ; Boison ). Finally, very recent evidence has shown a role for the endocannabinoid system in regulating susceptibility to epilepsy (reviewed in Soltesz et al .…”
Section: Synapse Dysfunction In Neurodevelopmental Disordersmentioning
confidence: 99%
“…In addition, disruption of adenosine and D‐serine signaling mechanisms associates with post‐synaptic molecular changes and lower seizure threshold (Klatte et al . ; Boison ). Finally, very recent evidence has shown a role for the endocannabinoid system in regulating susceptibility to epilepsy (reviewed in Soltesz et al .…”
Section: Synapse Dysfunction In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Recently, Klatte and colleagues (Klatte et al . ) found in an experimental model of TLE that memory defects are associated with a reduction in the CNS levels of d ‐serine because of decreased synthesis by SR and increased degradation by DAAO (Klatte et al . ).…”
Section: Structure and Subunit Diversity Of Nmdars In The Cnsmentioning
confidence: 99%
“…) found in an experimental model of TLE that memory defects are associated with a reduction in the CNS levels of d ‐serine because of decreased synthesis by SR and increased degradation by DAAO (Klatte et al . ). This weaker d ‐serine content leads to a desaturation of the co‐agonist binding site of synaptic and extrasynaptic NMDARs which in turn results in severe LTP impairment and spatial learning deficits in epileptic animals (Klatte et al .…”
Section: Structure and Subunit Diversity Of Nmdars In The Cnsmentioning
confidence: 99%
“…For example, D-serine potentiates NMDA-induced convulsions but antagonizes electroshock-induced tonic-clinic seizures in mice. 40) Regardless of whether M22 affects NMDA receptors, however, our results showed that M22 ultimately elevated the seizure threshold in the mouse maximal electroshock model. Additional evidence is required to establish the role of the strychnine-insensitive binding site in the pathogenesis of seizures.…”
Section: Discussionmentioning
confidence: 65%